Optimisation of nickel based catalyst formulation and operating variables for dry reforming of methane using response surface methodology approach - Abdul Hadi, Abdullah (2024)
The conversion of methane and carbon dioxide into synthesis gas through dry reforming, which targets two prevalent greenhouse gases (CH4 and CO2), has garnered significant interest in recent times. This process offer notable advantage as it facilitates the production of synthesis gas with an optimal H2/CO ratio suitable for Fischer-Tropsch synthesis. Studies concerning nickel catalysts employed in this reaction have primarily concentrated on assessing the intrinsic activity of the metal phase, its stability against carbon deposition, identifying the most suitable support for enhancing catalyst efficiency, and elucidating the reaction mechanism. Despite the substantial advancements in nickel catalyst development, which have demonstrated remarkable activity from an industrial perspective, these catalysts undergo complete deactivation within a short period of reaction time due to the formation of stable and inactive carbon on their surface. The study aims to meet the need for a full understanding of the best catalyst formulation and reaction conditions for an effective dry reforming of methane (CH4). Catalysts were made using a mix of Nickel (Ni), Cobalt (Co), Magnesium (Mg), and NaA zeolite support. BoxBehnken Design-Response Surface Methodology (BBD-RSM) was used optimised the catalyst formulation and reaction condition for DRM and evaluated the effect of variables to the reactant conversion and H2/CO ratio. The Box-Behnken Design-Response Surface Methodology (BBD-RSM) was utilized to optimize the catalyst formula and reaction conditions for DRM. BBD-RSM was also applied to assess how variables affected reactant conversion and the H2/CO ratio. Basic characterization techniques were employed to confirm the findings from BBD-RSM. Additionally, a study on catalyst stability was conducted to assess the durability of the synthesised catalyst. The ideal composition of the NaA zeolite support catalyst was found to consist of 9.91% nickel, 8.84% cobalt, and 1.62% magnesium loadings. At optimal formulation, the catalyst demonstrated methane (CH4) conversion of 21.9%, carbon dioxide (CO2) conversion of 33.5%, and with hydrogen to carbon monoxide (H2/CO) ratio of 0.904. The simulation and experimental data exhibiting less than 10% error. The optimum reaction conditions for biogas dry reforming using the 9.8Ni8.2Co1.8Mg/NaA zeolite catalyst were found to be a reaction temperature of 700°C, reduction temperature of 650°C, and a gas hourly space velocity (GHSV) of 10000 h-1 . At ideal condition, the catalyst showed 64% CH4 conversion, 83% CO2 conversion, and with 1.18 H2/CO ratio. The 9.8Ni8.2Co1.8Mg/- NaA zeolite catalyst could withstand 96 hours on stream with final feed conversion at 40% for CH4 and 55 % for CO2. The kinetics and reaction mechanism of the dry reforming process using the 9.8Ni8.2Co1.8Mg/NaA zeolite catalyst was also investigated. The reaction mechanism was found to be consistent with the Eley-Rideal model, in which the reaction occurs between activated CO2 on the catalyst surface and CH4 in the gas phase. The temperature sensitivity analysis shows activation energy values of 46.53, 39.66, 46.65, and 34.49 kJ/mol for CH4 consumption, CO2 consumption, H2 formation, and CO formation, respectively, indicating the CH4 dissociation step could be the reaction rate determining step and the occurrence of the reverse water gas shift (RWGS) side reaction. This study presents a novel approach to dry reforming of methane (DRM) using a catalyst comprising nickel, cobalt, magnesium, and NaA zeolite, a combination previously unexplored. The research holds significant environmental, economic, and social implications. The optimised methane reforming process contributes to sustainability by utilising natural resources and reducing greenhouse gas emissions. Moreover, the study advances knowledge in catalysis and renewable energy technologies, paving the way for further research and development in the field